PELATIHAN DIGITAL MARKETING SEBAGAI STRATEGI PENGUATAN EKONOMI KELUARGA - Rizqi Noerrachman; Yunike Berry; Isti Puji Hastuti (Universitas Islam 45 Bekasi, 2022)
The purpose of this activity is to increase the knowledge of MSME actors in utilizing the internet and technology to support the marketing of their products and to encourage MSME actors to transform into online markets in order to expand the reach of their target market or consumers through digital marketing. In the current era of the Covid-19 Virus, the income of MSME actors is reduced because consumers prefer to shop online rather than in person. SMEs must find the right strategy to increase their sales during the pandemic in order to survive. The programs that have been implemented are: (1) Socializing the Importance of Online Marketing, (2) Training on Account Creation/Marketplace Stores, and (3) How to Upload Products. Which will be held in February 2022 at Mega Regency Blok H RT 005/RW 009, Sukasari Village, Serang Baru District, Bekasi Regency. By using the Hybrid method. Through the above activity program, MSME actors have become more aware of selling online on the marketplace in order to increase product sales and strengthen the family economy during the current pandemic.